Changes in the utilization of psychiatric hospital facilities in Denmark by patients diagnosed with schizophrenia from 1970 through 2012: The advent of 'revolving door' patients. (8th January 2016) - Jeppesen, R. M.; Christensen, T.; Vestergaard, C. H.
Abstract : Objective: The Danish psychiatric system has gone through several structural changes in the last four decades. The deinstitutionalization of the mental healthcare system was implemented in Denmark in the late 1970s with the intention of increasing out‐patient treatment. One of the aims in the reorganization was to treat the patient in the local environment rather than during long‐term hospitalization. This study focuses on the changes in the utilization of hospital facilities. Method: Using register data from secondary healthcare treatment of patients diagnosed with schizophrenia in Denmark 1970–2012, we analysed the development in the use of hospital facilities. Results: Our major finding was a 220% increase between 1970 and 2012 in the total number of hospital admissions due to schizophrenia each year, while at the same time the number of annual schizophrenia bed days was reduced by 76%. Furthermore, the readmission rate within a year after discharge with a diagnosis of schizophrenia reached 70% in 2012 compared to 51% in 1970. Finally, the total bed occupancy continued to rise over the four decades and has exceeded 100% in several years since 1999. Conclusion: The findings indicate that the reorganization of the Danish mental healthcare system has created a problem of 'revolving door' schizophrenia patients' who since the 1970s have been increasingly hospitalized but for shorter periods. Possible explanations of the findings are premature discharge of patients with schizophrenia due to lack of beds or/and that community psychiatry has not been providing adequate relapse prevention.